A comparison on simulated, analytic, and measured impedance values for an inductive power transfer system. Issue 1 (19th March 2020) - Hassler, Marius; Atasoy, Oguz; Twelker, Karl; Kesler, Morris; Birkendahl, Johannes; Krammer, Josef
Abstract: Studies on inductive power transfer (IPT) systems are most times either theoretical or experimental. In this paper, we want to bring theoretical models and experimental data together using the impedance based interface proposed in SAE J2954. This proposal characterizes the IPT system by impedances at both coil terminals. We show how the experimental data was retrieved at the interface and use it to validate an analytical model and a Simulink model described within this study. Such models can support the design and development process and therefore a comparison with reality is necessary.